Single‐stage photovoltaic system design based on energy recovery and fuzzy logic control for partial shading condition. (17th January 2022) - Kandemir, Ekrem; Cetin, Numan Sabit; Borekci, Selim
Abstract: Multiple local maximum power points occur in the power–voltage characteristic curve of the photovoltaic (PV) systems due to use of bypass diodes under partial shading conditions, and this also leads to decrease the maximum power level of the PV system. This paper proposes an energy recovery‐based PV system to enhance maximum power level and working efficiency under partial shading conditions. In this study, a 350‐W PV system design and application, which can operate at maximum power point under partial shading condition, is made using two 175‐W PV panels. The main purpose of the system is to maintain power generation from the shaded PV panel by energy recovery circuit without any damage on the PV panels and also connect PV panels to the grid by single power circuit. To perform the maximum power point tracking (MPPT) task for the PV system, a single input variable used fuzzy logic control (FLC)‐based MPPT method is developed. Therefore, this study investigates and analyzes energy recovery connected and fuzzy logic control‐based MPPT controlled PV system under partial shading conditions. Effectiveness of the proposed system has been verified through simulation and experimental results. Abstract : This study introduces an implementation of the single‐stage photovoltaic (PV) system design connected energy recovery circuit that increases maximum available power and removes multiple maximum power points (MPPs) on the power–voltage characteristic curves. Additionally, a single input‐required fuzzy logic control (FLC)‐based MPP tracking (MPPT) is designed, which makes MPP tracking operation simple, quite stable, and less complexity. The proposed photovoltaic system provides 34% power increase for different partial shading scenarios compared with bypass mode operation according to the simulation and experimental results.